2007
DOI: 10.1016/j.cell.2007.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Regulation of Energy Metabolism by the Skeleton

Abstract: The regulation of bone remodeling by an adipocyte-derived hormone implies that bone may exert a feedback control of energy homeostasis. To test this hypothesis we looked for genes expressed in osteoblasts, encoding signaling molecules and affecting energy metabolism. We show here that mice lacking the protein tyrosine phosphatase OST-PTP are hypoglycemic and are protected from obesity and glucose intolerance because of an increase in beta-cell proliferation, insulin secretion, and insulin sensitivity. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

103
2,418
14
50

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,228 publications
(2,617 citation statements)
references
References 34 publications
103
2,418
14
50
Order By: Relevance
“…It has been established that mice lacking the osteocalcin gene had a phenotype that was obese, hyperglycemic, insulin-resistant, and glucose-intolerant. (16,17) Another study done in wild-type mice also observed the importance of osteocalcin in the regulation of glucose metabolism and fat mass. (18) At its simplest level, this relationship offers a plausible link between the established inverse relationship between body size, osteoporosis, and fracture risk.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been established that mice lacking the osteocalcin gene had a phenotype that was obese, hyperglycemic, insulin-resistant, and glucose-intolerant. (16,17) Another study done in wild-type mice also observed the importance of osteocalcin in the regulation of glucose metabolism and fat mass. (18) At its simplest level, this relationship offers a plausible link between the established inverse relationship between body size, osteoporosis, and fracture risk.…”
Section: Introductionmentioning
confidence: 96%
“…Targeted deletion of the osteocalcin gene results in a high BMD phenotype. (15) More recently, in a seminal paper by Lee and colleagues, (16) an additional role for OC as a hormone integral to the regulation of energy metabolism also has been identified. It has been established that mice lacking the osteocalcin gene had a phenotype that was obese, hyperglycemic, insulin-resistant, and glucose-intolerant.…”
Section: Introductionmentioning
confidence: 99%
“…RUNX2 has been identified as a ‘master gene’ in the differentiation of osteoblasts, serving as a key transcription factor that regulates extracellular matrix (ECM) gene products (e.g., osteocalcin, OCN) (Lee et al ., 2000; Tu et al ., 2008). OCN is secreted by osteoblasts, it is believed to play a role in the body's metabolic regulation, and it is pro‐osteoblastic (bone building; Lee et al ., 2007). OCN is therefore often used as a marker of bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…It is a small protein of 100 amino acids, and is secreted solely by osteoblasts. Functionally, osteocalcin is pro-osteoblastic and bone building by influencing mineralization (Lee et al, 2007). Osteocalcin can be modified post-translationally by carboxylation through the activity of a vitamin-K dependent carboxylase.…”
mentioning
confidence: 99%